TRAINING ON MARKETING MANAGEMENT AND DIGITAL-BASED PRODUCT PROMOTION FOR MSMES IN KAMPOENG REMITAN, MAYONG LOR VILLAGE, JEPARA REGENCY - Putri Purwaningrum, Jayanti; Purbasari, Imaniar; Puspita Rini, Gilang (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Kampoeng Remitan is an MSME in Mayong Lor Village, Jepara Regency which is engaged in pottery such as piggy banks, jugs, remittance children's toys, roof tiles, and others. The business that has been carried out by craftsmen in MSMEs has not been known for generations. Whereas the resulting product is one of the superior products of the local area. Lack of management in the field of marketing and promotion is one part of the cause. Whereas in the current era, digital-based marketing management and product promotion are very popular with many traders. Many MSME actors use the internet through social media or websites as a business field with good turnover prospects. Thus, the purpose of this training activity is the need for MSMEs in Kampoeng Remitan, Mayong Lor Village, and Jepara Regency to adapt to technological developments in terms of online or digital-based marketing and promotion. The existence of this activity is useful as an increase in the knowledge capacity, ability, and competence of craftsmen in terms of using the internet as a digital marketing, promotion, and sales medium.